Dinamika Partisipasi Guru dan Siswa dalam Proses Pengambilan Keputusan di Sekolah - Handoko, Yudo; Ramadhoni, Sri Rahmah; Fitriana, Fitriana; Tersta, Friscilla Wulan (SAP (Susunan Artikel Pendidikan), 2025)
The objective of this study is to explore the participation of teachers and students in decision-making processes at SMA Negeri 4 Tanjung Jabung Timur. A qualitative approach, utilizing a case study method, was employed to examine the communication dynamics within the school, incorporating in-depth interviews, observations, and document analysis. The findings reveal that teacher and student participation in decision-making remains limited, with decisions often dominated by school management without substantial input from either group. Teachers expressed that their suggestions were rarely considered, while students reported similar experiences, particularly concerning extracurricular activities. Communication barriers such as the absence of formal discussion forums and inadequate policy dissemination were also noted. Additionally, the use of communication technology at the school was mostly restricted to administrative notifications, rather than facilitating inclusive two-way discussions. The study identified several factors contributing to this low participation, including centralized leadership, limited opportunities for dialogue, and a communication culture that does not actively support engagement. To improve participation, the study recommends strategies such as increasing formal discussion forums, leveraging technology for interactive communication, and adopting more inclusive leadership practices. These strategies are expected to enhance teacher and student involvement in decision-making, fostering a more democratic and collaborative school environment.